„PROSTA MOWA” W TEKSTACH O CHARAKTERZE RELIGIJNYM XVIII WIEKU (NA PODSTAWIE WYDAŃ TREBNIKÓW W DRUKARNIACH BAZYLIAŃSKICH) - Getka, Joanna (Acta Neophilologica, 2016)
This article analyzes fragments of texts written in the prosta mova found in trebnyks printed by the Basilians. These fragments testify to the presence of the prosta mova in the church. They also confirm the opinions concerning the faint understanding of the Church Slavonic language by ordinary followers. In order for the faithful to able to consciously participate in various sacraments, the texts contained in the trebnyks were adapted to local language reality. The Basilian trebnyks that are subject to analysis in this article (except for the one printed in Supraśl) are very similar to the Orthodox Trebnyk by P. Mohyla, referred to here as relevant to the context of the problem. The fact that the Basilians followed Mohyla’s pattern so eagerly contradicts the emerging theories that the Basilian Order was engaged solely in the Polonisation activities.